(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
In the second crop, the highest marketable yield was obtained from the pumpkin varieties Red Gowed (42.7 t/ha), No. 17731 (40.9 t/ha), and Orginal (40.7 t/ha), and the highest net profit and profitability were obtained from the pumpkin varieties Red Gowed (60.7 mln soums and 245.6%), No. 17731 (57.2 mln soums and 232.2%), Orginal (56.8 mln soums and 230.7%), No. 16338 (50.7 mln soums and 207.5%), and Maki (45.5 mln soums and 187.0%).